Distribution and population structure of deep‐dwelling red coral in the Northwest Mediterranean. (15th July 2015) - Angiolillo, Michela; Gori, Andrea; Canese, Simonepietro; Bo, Marzia; Priori, Cristina; Bavestrello, Giorgio; Salvati, Eva; Erra, Fabrizio; Greenacre, Michael; Santangelo, Giovanni
Abstract: Commercially harvested since ancient times, the highly valuable red coral Corallium rubrum (Linnaeus, 1758) is an octocoral endemic to the Mediterranean Sea and adjacent Eastern Atlantic Ocean, where it occurs on rocky bottoms over a wide bathymetric range. Current knowledge is restricted to its shallow populations (15–50 m depth), with comparably little attention given to the deeper populations (50–200 m) that are nowadays the main target of exploitation. In this study, red coral distribution and population structure were assessed in three historically exploited areas (Amalfi, Ischia Island and Elba Island) in the Tyrrhenian Sea (Western Mediterranean Sea) between 50 and 130 m depth by means of ROV during a cruise carried out in the summer of 2010. Red coral populations showed a maximum patch frequency of 0.20 ± 0.04 SD patches·m −1 and a density ranging between 28 and 204 colonies·m −2, with a fairly continuous bathymetric distribution. The highest red coral densities in the investigated areas were found on cliffs and boulders mainly exposed to the east, at the greatest depth, and characterized by medium percentage sediment cover. The study populations contained a high percentage (46% on average) of harvestable colonies (>7 mm basal diameter). Moreover, some colonies with fifth‐order branches were also observed, highlighting the probable older age of some components of these populations. The Ischia population showed the highest colony occupancy, density and size, suggesting a better conservation status than the populations at the other study locations. These results indicate that deep dwelling red coral populations in non‐stressed or less‐harvested areas may diverge from the inverse size‐density relationship previously observed in red coral populations with increasing depth.